The Problem of Sources and the Repertoire of Gottfried Ostermeyer’s Hymnal (1781) - Strungytė-Liugienė, Inga (Senoji Lietuvos literatūra, 2016)
The paper addresses the issue of the German sources that Gottfried Ostermeyer (1716–1900) might have used when translating new hymns for the Evangelical Lutheran hymnal Giesmes ßwentos Baźnyczoje ir Namej’ giedojamos (Holy Hymns Sung in Church and at Home; Königsberg, 1781). It also overviews the trends of repertoire selection for this hymnal. As the original hymnal has not been found yet (or has not survived), the research is based on a secondary source, the hymnal Wissokies Naujes Giesmes arba Ewangelißki Psalmai (Various New Hymns or Evangelical Psalms; Tilsit, 1817) by Kristijonas Endrikis Mertikaitis (c. 1775–1856). It contains over fifty hymns by Ostermeyer and his colleagues Paul Schröder (1723–1796) and Christian Lovin (1721–1783), both pastors from Lithuania Minor. Important for the reconstruction of the history of Ostermeyer’s hymnal are references to earlier-published hymnodal works in his polemical works and in the history of Lithuanian hymnals in Erste Littauische Liedergeschichte (The First History of Lithuanian Hymns; Königsberg, 1793). Quotations and quotationlike fragments of other authors recognized in these works point to the books owned by Ostermeyer and to his attitudes and interests. Of 45 translated hymns, over 30 are associated with Michael Lilienthal’s official hymnal of Königsberg Vernünftiger Gottesdienst des Singens (the 1752 or earlier edition) cited in Erste Littauische Liedergeschichte and in polemical works. One hymn – Ludwig Andreas Gotter’s hymn about faith ‘Dußios mano Netikuma’ – was translated by Ostermeyer from the German church hymnal of Mitau (Lith. Mintauja, now Jelgava) Mitauisches Gesangbuch (The Hymnalbook of Mitau; Mitau, 1769– 1771?) or its later edition of 1778 compiled by Christian Huhn and Johann Friedrich Kasimir Rosenberger. The surviving corpus of hymns of Ostermeyer’s hymnal shows that the author preserved the traditions of East Prussian liturgical communal singing and observed the regional trends. Translations of works by such seventeentheighteenth-century religious poets as Simon Dach and Georg Weisel from the Königsberg area, the Baroque author Paul Gerhard, the Halle pietists Jacob Gabriel Wolf and Joachim Lange, the advocate of the Lutheran orthodoxy Johann Friedrich Mayer and others reflect the common principles of compilation and selection of the repertoire for Königsberg hymnals. However, Ostermeyer wanted to reform the hymnal and thus added hymns which were not included in eighteenth-century German hymnals of Königsberg. Inclusion of the hymns by Benjamin Schmolck (1672–1737), the senior court preacher of Schweidnitz (now Świdnica, Poland) into the Lithuanian hymnal demonstrates Ostermeyer’s courage and determination for renewal and expansion of the boundaries of the regional repertoire.